Ethical guidance for health research in prisons in low- and middle- income countries: a scoping review (2020)
Objectives: This study examined the extent, range and nature of the published literature, prison policies and technical guidance relating to the ethical conduct of health research in prisons in low- and middleincome countries (LMICs). Study design: Scoping Review. Methods: We adhered to the five stages of the scoping review iterative process: identifying the research question, identifying relevant studies, study selection, charting the data, and collating, summarizing and content analysis of polices. Disagreements around allocation of content were resolved through team discussion. We also appraised the quality of the included articles. Results: We included nine records that examined the ethical aspects of the conduct of health research in prisons in LMICs; eight of these were peer-reviewed publications, and one was a toolkit. Despite the unique vulnerabilities of this group, we could find no comprehensive guidelines on the ethical conduct of health research in prisons in LMICs. Conclusions: The majority of the world's imprisoned populations are in LMICs, and they have considerable health needs. Research plays an important role in addressing these needs and in so doing, will contribute to the achievement of the Sustainable Development Goals. With regards to health research, imprisoned people in LMICs are ‘left behind’; there is a lack of clear, prison-focused guidance and oversight to ensure high quality ethical health research so necessary in LMICs. There is an urgent need for prison health experts to work with health research ethics experts and custodial practitioners for procedural issues in the development of prison-specific ethical guidance for health research in LMICs aligned with international standards.